A dimensão religiosa hare-krishna na Paraíba. - Ribeiro, Saulo Duarte Lima (2015)
The Hare-Krishna movement, classified as an orthodox Vedantist Hinduism type (also called Vaishnava Movement), is considered of utmost importance in the Western religions, not only because of its rapid growth and influence, but mainly because of its constantly highlighted as exotic appearance. Considered the core of Hinduism, the Movement is being disseminated in almost every country and main cities of the world. Arriving in Brazil on the seventh decade brougth by A.C. Bhaktivedanta Swami Prabhupãda, the "hares"(as they are also called the devotee) had good receptivity from the occidental public. The Movement starts to form small coexistence spaces in São Paulo, Rio de Janeiro and Salvador, after spreading to Recife, where they established the first temple, in the end of the seventh decade. Arriving to Paraíba in the beginning of the eighth decade, years later the group open its temple and, also influenced by the New Conscience Meetings, held in Campina Grande, lately its seminary, this last one being the only one from the Movement in Brazil.